Seismic design of Xiluodu ultra-high arch dam - Ren-kun Wang (Water Science and Engineering, 2018)
The 285.5 m-high Xiluodu Arch Dam is located in a seismic region along the Jinsha River in China, where the horizontal components of peak ground accelerations for design and checking earthquakes have been estimated to be 0.355g and 0.423g, respectively (g is the gravitational acceleration). The ground motion parameters of design and checking earthquakes are defined by exceedance probabilities of 2% over 100 years and 1% over 100 years, respectively. The dam shape was first selected and optimized through static analysis of the basic load combinations, and then adjusted after taking into account the seismic loads. The dam should be operational during and after the design earthquake with or without minor repairs, and maintain local and global stabilities during an extreme earthquake. Both linear elastic dynamic analysis and nonlinear dynamic analysis considering radiation damping, contraction joints, and material nonlinearity were conducted to assess the stress in the arch dam. The dynamic analysis shows that the maximum dynamic compressive stresses are less than the allowable levels, while the area with tensile stress over the limit is less than 15% of the dam surface and the maximum contraction openings range from 10 mm to 25 mm. The arch dam has sufficient earthquake-resistance capacity and meets the safety requirements. Nevertheless, steel reinforcement has been provided at the dam toe and in the zones of high tensile stress on the dam surface out of extra precaution. Keywords: Seismic design, Nonlinear dynamic analysis, Dam shape optimization, Seismic strengthening, Xiluodu arch dam